Integrating Project-Based Learning and Place-Based Education on Renewable Energy to Enhance Students’ Creativity and Environmental Awareness - Siti Rukoyah; Anna Permanasari; Surti Kurniasih (AL-ISHLAH: Jurnal Pendidikan, 2025)
Developing students’ creativity and environmental awareness is essential in sustainability-oriented science education. Integrating Project-Based Learning (PjBL) with a Place-Based Education (PBE) framework offers a promising approach by connecting classroom learning with real-world environmental contexts. This study employed a quasi-experimental design using a pretest–posttest control group. The sample consisted of 74 junior high school students in Bogor, Indonesia, including 35 students in the control group and 39 students in the experimental group. The experimental group received PjBL integrated with PBE, while the control group implemented PjBL without a place-based framework. Data were collected using creative thinking tests, environmental awareness questionnaires, observation sheets, and response questionnaires from students, teachers, and community members. Instrument validity and reliability were confirmed through preliminary testing. The results indicated that the PjBL–PBE model was highly implementable and effective. Students’ creative thinking skills in the experimental group showed a higher improvement (N-Gain = 56.18%) compared to the control group. Environmental awareness also increased substantially in the experimental group (67.15%), while the control group showed only a modest improvement (13.62%). Stakeholder responses demonstrated strong support for the learning model (91.60%). These findings suggest that integrating PjBL with a place-based framework effectively enhances students’ creative thinking and environmental awareness in renewable energy education.